2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1721.r1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic tilt from supine to standing in patients with symptomatic acetabular retroversion of the hip

Abstract: Aims Acetabular retroversion is a recognized cause of hip impingement and can be influenced by pelvic tilt (PT), which changes in different functional positions. Positional changes in PT have not previously been studied in patients with acetabular retroversion. Methods Supine and standing anteroposterior (AP) pelvic radiographs were retrospectively analyzed in 69 patients treated for symptomatic acetabular retroversion. Measurements were made for acetabular index (AI), lateral centre-edge angle (LCEA), crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The change in pelvic tilt from supine to standing demonstrated in this study is in keeping with previous research into the relationship of pelvic tilt with AR. A previous study from our institution reported a low pelvic tilt angle in the supine position which contributed to the appearances and symptoms of retroversion, 10 and a change in pelvic tilt from supine to standing has previously been extensively reported at a similar magnitude to this study in patients with hip dysplasia. 18,20,21 The correction in pelvic tilt required to orientate the CT images between APP and supine or standing positions has not previously been reported.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The change in pelvic tilt from supine to standing demonstrated in this study is in keeping with previous research into the relationship of pelvic tilt with AR. A previous study from our institution reported a low pelvic tilt angle in the supine position which contributed to the appearances and symptoms of retroversion, 10 and a change in pelvic tilt from supine to standing has previously been extensively reported at a similar magnitude to this study in patients with hip dysplasia. 18,20,21 The correction in pelvic tilt required to orientate the CT images between APP and supine or standing positions has not previously been reported.…”
Section: Discussionsupporting
confidence: 80%
“…It has been suggested that acetabular retroversion results from an external rotation of the hemipelvis, which has previously been described after analysis of plain radiographs 5 and CT imaging of patients with hip dysplasia. 6 It is also well accepted that the pelvic position, particularly in terms of rotation in the sagittal plane, does significantly affect the appearance and interpretation of plain radiological signs, [7][8][9][10] as well as measurements from cross-sectional imaging. 3,11,12 In order to counteract this, imaging analysis is often preceded by correction of pelvic sagittal rotation to a predetermined plane.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients experiencing anterior impingement might exhibit pelvic retroversion as a compensatory mechanism to alleviate pain, a situation that could potentially result in dynamic acetabular anteversion. 3 It has been reported that patients within the instability group experienced instances of femoral/acetabular version, as discussed earlier. Nonetheless, a commentary by Hohmann 2 proposed that excessive femoral anteversion and anterior acetabular undercoverage could be risk factors for unfavorable outcomes, potentially prompting acetabular anteversion as a compensatory response.…”
mentioning
confidence: 77%
“…9-13 Surgeons who undertake this procedure must recognize that changes in the sagittal profile and balance could influence decisions about the functional orientation of the acetabular component. 14 Additionally, the classification proposed by Tang et al 1 may provide valuable insights into the longstanding debate regarding the sequence of surgical interventions – whether to address the hip or spine first in patients presenting with significant symptoms in both areas. For some of these patients, all compensatory reserves will have been exhausted, making THA unlikely to rectify the global balance significantly.…”
mentioning
confidence: 99%